Ferroelectric glass-ceramics from the PbO-Bi2O 3-GeO2 system - A. Munpakdee (2018)
The glass ceramics from the PbO-Bi3O2-GeO2 system have been investigated. An excellent transparent glass can be obtained from the stoichiometric (S) composition, Pb3Bi2(GeO 4)3, but only by rapid-quenching to give very thin samples. This glass could not therefore be used to make good glass-ceramic samples for measuring the dielectric properties. The A-composition (34.50%PbO :11.49%Bi2O3: 54.01%GeO2) and B-composition (25.90%PbO: 8.63%Bi2O3: 65.47%GeO2) have been prepared to form more stable glasses. These two compositions gave good transparent and thick glass samples. DTA analysis has been used to examine the crystallisation temperatures of all glasses. The controlled heat treatment process has been applied to all crystallisation temperatures and glass-ceramic samples were obtained. It was found that S glassceramic contained Pb 3Bi2(GeO4)3 and Bi 2GeO5 while A glass-ceramic contained only Pb 3Bi2(GeO4)3 and was suitable for using in dielectric measurement. B glass-ceramic gave difficulty in identifying the phases. However, it was concluded that the glass-ceramic from this composition had three phases, which are PbGe4O9, PbGeO5 and Bi4(GeO4)3. Since this glass gave no PbO-Bi2O3-GeO2 ternary phase, the dielectric measurement concentrates only on the A glassceramic. The frequency dependence of ε" for the A glass-ceramic sample gave a loss peak at low frequency. © 2008 Trans Tech Publications, Switzerland.